PERAN PEMERINTAH DAERAH TERHADAP PENANGGULANGAN KORBAN BENCANA ALAM GUNUNG KELUD DI KECAMATAN NGLEGOK KABUPATEN BLITAR - PUSPARINI, YUNASTITI (Jurnal Akuntansi AKUNESA, 2014)
This study aimed to determine the role of local government to the victims of natural disaster relief in the district Kelud Nglegok Blitar. The government has an active role to victims of natural disasters ranging from pre-disaster, emergency response to the disaster. Government preparedness is an important step in the prevention of natural disasters . The method used in this research is descriptive method of data collection using data triangulation consisting of interviews Nglegok Blitar district, interviews with the Head of the District Nglegok Blitar and secondary data obtained from BPBN. The results showed that the role of local governments on disaster mitigation Kelud on Nglegok Blitar district very well. This is evident from the absence natural disaster victims Kelud. All of people in Nglegok also very cooperative in the face of disaster. So that evacuation can proceed smoothly without a hitch.   Keywords : role of government, disaster of Kelud